Computational Results With Non-singular and Non-local Kernel Flow of Viscous Fluid in Vertical Permeable Medium With Variant Temperature - Riaz, Muhammad B.; Saeed, Syed T.; Baleanu, Dumitru; Ghalib, Muhammad M. (Frontiers in Physics, 2020)
Unsteady electrically conducting viscous fluid flow with transversal magnetic field in porous medium over vertical wall with ramped temperature has studied with Atangana-Baleanu derivative. Conjugate impact of heat and mass transfer with slip and non-slip effect are considerable. Solutions of governing equations for temperature gradient, concentration gradient and velocity profile are obtained with Laplace transformation. Inversion calculation of Laplace transformation have been computed with Stehfest’s algorithm. Computational results have been expressed graphically with the effect of various flow physical parameters. Comparative graphical analysis with existing literature as well as Atangana-Baleanu derivative for temperature, concentration and velocity field with slip and non-slip impact shows that the memory effects of Atangana-Baleanu derivative are better than the results existing in literature.